Project Based Learning (PjBL) Model with STEM Approach on Students’ Conceptual Understanding and Creativity - Prajoko, S.; Sukmawati, I.; Maris, A. F.; Wulanjani, A. N. (Jurnal Pendidikan IPA Indonesia, 2023)
The starting point of this research is the absence of understanding of students’ conceptions of the human movement system material, as well as students’ unformed creativity. This study aims to analyze the effect of the STEM-approach PjBL model on students’ conceptual understanding and creativity. This research was quantitative research with a quasi-experimental method with a post-test-only control design type. The sampling used a purposive sampling technique. The instruments used were concept comprehension tests, syntax implementation observation sheets, and creativity questionnaire sheets. The paired sample t-test was used to analyze the data. Based on data analysis, the average post-test results for the experimental and control classes are 83.44 and 79.14, respectively. The data analysis of the student creativity questionnaire results suggest that 19 students are quite creative. The paired t-test result for students’ concept understanding is 0.002, indicating that the research hypothesis is accepted, while the result for creativity is 0.64. With moderate criteria, the PjBL model with the STEM approach effects students’ conceptual understanding and creativity.